Gender imbalance at birth and parents' anxiety about old age in China - Yoshihiko Kadoya; Ting Yin (Osaka University, Institute of Social and Economic Research (ISER), 2012)
Chinese parents prefer to have sons as they depend on their sons for support in old age, according to most of the literature. This paper uses the Preference Parameters Study, which randomly interviewed individuals in six major cities in China in 2011, to present empirical evidence about the possible cause of the problematic gender imbalance at birth in China. From the dataset, this paper compares sons' and daughters' commitment to parental care from a selection of respondents who were married, aged 20-70, had at least one living parent, and had no missing answers to the interview questions. The results indicate that Chinese sons (and their wives) are more likely, compared to daughters (and their husbands), to be primary caregivers for parents. Nonetheless, parents' dependency on their children would not necessarily decrease with social security, although children with highly educated spouses appear to present an exception. The current study supports the initial claim found in literature; however, the solution to the gender imbalance at birth in China may not be the development of a social security system.
Keywords: P29; J16; 330; gender imbalance; anxiety about old age; family caregiving; son preference; China; Familienplanung; Familienpflege; Kinder; China